PENGARUH BIAYA PENDIDIKAN PERSONAL DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS VIII PADA MATA PELAJARAN IPS TERPADU DI SMPN 3 XIII KOTO KAMPAR - Rahmawati, Santi; Indrawati, Henny; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to find out how much personal education costs and motivation to learn about the learning outcomes of grade VIII students on integrated IPS courses at SMPN 3 XIII Koto Kampar. This research is a quantitative descriptive study using multiple linear regression analyses with the SPSS aid program. The sampling technique proportionate random sampling with a sample number of 66 students. Research instruments using poll. The results showed that the cost of personal education and the learning motivation of students both included in the medium category, while the results of learning in the category are sufficient. From the test results gained that the cost of education and motivation studied significantly towards student learning outcomes. That means that if the cost of education and motivation to learn high students, students ' learning outcomes will be good too. A partial cost of personal education has a positive effect and is not a significant impact on student learning outcomes. When the cost of personal education has increased, it will not necessarily improve student learning outcomes because of the influence of the cost of education is very weak towards student learning outcomes. Meanwhile, the motivation for learning has a positive and significant influence on student learning outcomes, meaning the better the student's learning motivation, the better the student learning outcomes.Key Words: Education, Personal Motivation, Learning, Learning Outcomes, Integrated IPS